Mastering The Concept of Live Shopping Strategy at Kamar Dagang dan Industri Kota Bandung in Order to Increase Sales Volume - Arissaputra, Rivaldi; Azizah Asmara, Maisa; Felinda Amalia, Tiara (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Live shopping is one approach to marketing methods. However, this strategy requires a deep understanding of the conditions of its partners, especially for those who are just starting out, requiring technological knowledge as well as an understanding of consumer behavior and regional market dynamics. This Community Service activity aims to improve the understanding and skills of MSMEs in Bandung City in utilizing digital marketing strategies through live shopping. A total of 16 MSME partners participated in this program, the research method designed included two stages, namely needs analysis and counseling related to business model changes and digital consumer behavior. The evaluation results showed that 80% of the partners successfully surpassed the post-test threshold score of 70, with an average understanding above 70%. From the 15 questions asked, feedback shows that partners have a good understanding of the concept of live shopping, the influence of technology in marketing, and the importance of understanding consumer behavior. This activity is expected to make a significant contribution in improving the competitiveness of MSMEs, as well as encouraging innovation in marketing local products in the digital era.